'Not as single spies': a review of European Social Anthropology 2020. (1st November 2021) - Martin, Dominic
Abstract : This review article surveys all of the articles published in the major Anglophone European social anthropology journals in 2020. Taking a perspective from Joel Robbins' theorising of 'the anthropology of the good' as a critique of the primacy of 'dark anthropology', it highlights the rich range of ethnography and analysis recently produced. Focusing on the continuing interest in ontology, environment, relations and the problems inherent in anthropological comparison, the review article identifies how – during the crisis of the COVID‐19 pandemic – the discipline has continued to respond with vigour and resilience. An ongoing resurgence of the anthropology of religion is noted, as is the emergence of powerful emic exploration of such global phenomena as care, debt and corporate capitalism. The review article concludes with a reflection on the ideological and epistemological challenges social anthropology continues to face, both in the academy and more widely.